Bengamide Analogues Show a Potent Antitumor Activity against Colon Cancer Cells: A Preliminary Study - García-Pinel, Beatriz; Porras Alcalá, Cristina; Cabeza, Laura; Ortiz, Raul; Prados, José; Melguizo, Consolación; Cheng-Sánchez, Iván; López-Romero, Juan Manuel; Sarabia-García, Francisco Ramón (My University, 2020)
The limited success and side effects of the current chemotherapeutic strategies against colorectal cancer (CRC), the third most common cancer worldwide, demand an assay with new drugs. The prominent antitumor activities displayed by the bengamides (Ben), a family of natural products isolated from marine sponges of the Jaspidae family, were explored and investigated as a new option to improve CRC treatment. To this end, two potent bengamide analogues, Ben I and Ben V, were selected for this study, for which they were synthesized according to a new synthetic strategy recently developed in our laboratories. Their antitumor effects were analyzed in human and mouse colon cell lines, using cell cycle analysis and antiproliferative assays. In addition, the toxicity of the selected analogues was tested in human blood cells. These biological studies revealed that Ben I and V produced a significant decrease in CRC cell proliferation and induced a significant cell cycle alteration with a greater antiproliferative effect on tumor cell lines than normal cells. Interestingly, no toxicity effects were detected in blood cells for both compounds. All these biological results render the bengamide analogues Ben I and Ben V as promising antitumoral agents for the treatment of CRC.
Keywords: Antineoplásicos; bengamides; synthesis; antitumor agents; colorectal cancer